2007
DOI: 10.1080/10428190701665970
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel and filgrastim for hematopoietic progenitor cell mobilization in patients with hematologic malignancies after failure of a prior mobilization regimen

Abstract: Paclitaxel and G-CSF have been evaluated for HPC mobilization in breast cancer and found to have tolerable toxicity with a predictable time to initiate leukapheresis. However, this approach has not been reported in patients with hematologic malignancies failing prior mobilization. We report a case-series of 26 adults given paclitaxel and G-CSF for HPC mobilization after failure of an initial mobilization. Patients received paclitaxel 250 mg/m(2) followed by G-CSF 10-16 mcg/kg/day. Compared to the initial regim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…6 The present study has shown that the upward trend was confined to males diagnosed with lymphoid leukemia at ages 1-4 years. Current epidemiological evidence suggests a role for infections in etiology, 6 possibly in combination with other environmental agents.…”
Section: Sex-specific Patterns and Trends In The Incidence Of Hematolmentioning
confidence: 85%
See 3 more Smart Citations
“…6 The present study has shown that the upward trend was confined to males diagnosed with lymphoid leukemia at ages 1-4 years. Current epidemiological evidence suggests a role for infections in etiology, 6 possibly in combination with other environmental agents.…”
Section: Sex-specific Patterns and Trends In The Incidence Of Hematolmentioning
confidence: 85%
“…Additionally, pre-clinical and clinical studies show that acute myeloid leukemia, and chronic lymphocytic leukemia cells may be mobilized by AMD3100 via CXCR4 inhibition, [8][9][10] thus limiting the use of this agent in patients with certain hematologic malignancies. Our findings show that paclitaxel is effective in mobilization of PBSC in patients with hematologic malignancies, not only as salvage therapy, 6 but also in patients with adverse prognostic factors for mobilization. The overall mobilization success rate was 75%, being lower in acute leukemia (44%) than in other hematologic malignancies (83%).…”
Section: Group a Patients Treated With Paclitaxel-rhg-csf (P-g) As Fmentioning
confidence: 88%
See 2 more Smart Citations
“…For this reason, patients responding to TTR were given a cycle of rituximab plus ifosphamide and etoposide to mobilize stem cells prior to collection. However, other investigators have subsequently utilized taxane‐based chemotherapy approaches for successful chemo‐mobilization in patients with relpased lymphomas (McKibbin et al , ; Sinha et al , ; Sinha et al , ).…”
Section: Discussionmentioning
confidence: 99%